Influência de protocolos de treino de equilíbrio no desempenho funcional de idosas com osteoporose - Ruzene, Juliana Rodrigues Soares [UNESP] (2014)
Objective: To investigate the effect of eight weeks of balance training with and without oscillation of vibratory pole and the effect of eight weeks of follow up muscle activation and in performance of elderly women with osteoporosis in balance scale. Method: 29 elderly women with osteoporosis participated in this study, randomly separated into two groups, Group Oscillatory Pole (GHO) (69.57 ± 5.81 years, n=14) with oscillation and Group Without Oscillatory Pole (CSO) (70.93 ± 7.43 years; n=15) without oscillation of the vibratory pole. Volunteers remained in four postures (Tanden, unipedal stance, standing position with reduced base support, and standing position with eyes closed and extended base support) for collecting the electromyographic signal (EMG) before and after training and eight weeks after its termination. Differentials active electrodes were placed in a bipolar configuration in, vastus lateralis (VL), biceps femoris (BF), tibialis anterior (TA), gastrocnemius lateralis (GL), gluteus maximus (GM), rectus femoris (RF) and lumbar iliocostalis (IL). EMG signal was analyzed by Matlab (Mathworks ® 7.0) in the time domain by calculating the linear envelope and the values were normalized by the peak activation of each muscle.The volunteers were evaluated for Berg Balance Scale before and after training and after follow up. For the classification of the level of physical activity of voluntary International Physical Activity Questionnaire was used. The normality of the data was verified by using the Shapiro Wilk test. Was used ANOVA two-way test repeated measures followed by Bonferroni post-hoc to determine the effect of training on balance test and muscle ativation, and for comparisons of sample characterization we used MANOVA test followed by Bonferroni post-hoc. Level of significance was 5%. Results: No significant differences were found in all comparisons between the data of muscle activation (p>0.05). In GHO was observed...